End-of-Life Skills and Professionalism for Critical Care Residents in Training: The ESPRIT Survey. (October 2021) - Arora, Samantha; Shaikh, Sameer; Karachi, Tim; Vanniyasingam, Thuva; Centofanti, John; Piquette, Dominique; Meade, Maureen; Boyle, Anne; Woods, Anne; Downar, James; Cook, Deborah
End-of-life (EOL) care is a key aspect of critical care medicine (CCM) training. The goal of this study was to survey CCM residents and program directors (PDs) across Canada to describe current EOL care education. Using a literature review, we created a self-administered survey encompassing 10 CCM national objectives of training to address: (1) curricular content and evaluation methods, (2) residents' preparedness to meet these objectives, and (3) opportunities for educational improvement. We performed pilot testing and clinical sensibility testing, then distributed it to all residents and PDs across the 13 Canadian CCM programs. Our response rate was 84.3% overall (77 [81.1%] for residents and 13 [100%] for PDs). Residents rated direct observation, informal advice, and self-reflection as both the top 3 most utilized and perceived most effective teaching modalities. Residents most commonly reported comfort with skills related to pain and symptom management (n = 67, 94.3%; score> 3 on 5-point Likert scale), and least commonly reported comfort with donation after cardiac death skills (n = 26-38; 44.8%-65.5%). Base specialty and time in CCM training were independently associated with comfort ratings for some, but not all, EOL skills. With respect to family meetings, residents infrequently received feedback; however, most PDs believed feedback on 6 to 10 meetings is required for competence. When PD perceptions of teaching effectiveness were compared with resident comfort ratings, differences were most apparent for skills related to pain and symptom management, cultural awareness, and ethical principles. By the end of their first subspecialty training year, PDs expect residents to be competent at most, but not all, EOL skills. In summary, trainees and programs rely on clinical activities to develop competency in EOL care, resulting in some educational gaps. Transitioning to competency-based medical education presents an opportunity to address some of these gaps, while other gaps will require more specific curricular intervention.